Boundaries of belonging : English Jamaica and the Spanish Caribbean, 1655-1715 - Hatfield, April Lee (Early American studies., 2023)
"Boundaries of Belonging shows how, in an early modern Caribbean of overlapping and contested borders, a mobile and diverse population that included pirates, smugglers, freedom seekers, and religious refugees, influenced theories of imperial belonging and interpolity law"--